Skin Tumors in Pediatric Patients with Xeroderma Pigmentosum: A Case Series - Aftab, Kanwal; Maqsood, Sidra; Yaqoob, Nausheen (Indian Journal of Medical and Paediatric Oncology, 2025)
Xeroderma pigmentosum (XP) is a rare autosomal recessive genetic disease. This disease predisposes patients to early-onset skin cancers, like squamous cell carcinoma and basal cell carcinoma. This was a 5-year experience. Here, we report nine pediatric cases of XP in which two patients had basal cell carcinoma and six patients had squamous cell carcinoma. We have also reported one case in which both skin malignancies were present. The subjects included seven boys and two girls, while seven subjects were from consanguineous marriages, and the average age was 9.4 years. All the patients had ulcerative budding tumor lesions on the face (eye, nose, chin, cheek, and forehead) and scalp. Squamous cell carcinoma is a common cutaneous malignancy related to XP in our study. Prevention is based on the early diagnosis of XP, skin photo-protection, screening and early treatment of lesions, and genetic counseling.
Keywords: basal cell carcinoma; squamous cell carcinoma; xeroderma pigmentosum; genetic disease; skin cancers